Sikap Konsumen terhadap Produk Donat Berbahan Mocaf Sebagai Pengganti Tepung Terigu (Studi Eksperimen pada Konsumen Donat di Universitas Muhammadiyah Yogyakarta) - Fadilah, Arsy Nur; Widodo, Widodo; Widodo, Aris Slamet (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2015)
The aims of this research were to identify consumer attitude toward all kinds of donut atribute which made from wheat flour and mocaf; and to compare consumer attitude toward all types ofÂ subtitution phase of donut. The respondents of this research were 45 respondents which accidentally taken from the buyers.Â The method of this research was eksperimental with the object were donut with 30% and 50% mocaf substitution ingredients and without mocaf substitution as a control. The data was gained in March 2015. Fishbein model was used to identify consumerâs attitude toward donut attribute which consist of taste, tekstur, shape, size, colour, and price; whereas Friedman test was used Â to compare consumers attitude toward donut with all types of substitution. The result of this research were showed that taste attribute and tekstur attribute was more considered in choosing donut product; and there was no significant difference in consumer attitude toward donut with mocaf substitution.